2017
DOI: 10.1108/ijaim-04-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Does the hiring of chief risk officers align with the COSO/ISO enterprise risk management frameworks?

Abstract: Purpose There are two main industry-sanctioned enterprise risk management (ERM) models, that is, COSO 2004 and ISO 31000:2009, that firms refer to when implementing ERM programs. Taken together, the two ERM models specify that firms should implement ERM programs to meet a strategic need, improve operations and reporting or to comply with government regulations or industry best practices. In addition, the focus of ERM implementation should be either the subsidiary, business unit, division, firm/entity or global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…3 The target period of the literature search extends up to October 2017, as at the time of writing this paper. Many studies discuss the advantages and disadvantages of ERM frameworks (Arena, Arnaboldi, & Azzone, 2010;Beasley, Clune, & Hermanson, 2005;Choo & Goh, 2015;Hayne & Free, 2014;Karanja, 2017;Paape & Speklé, 2012;Tekathen & Dechow, 2013), and many agree with the usefulness of COSO's ERM-IF. In Fraser, Schoening-Thiessen, and Simkins (2008) survey, 74% of respondents had read COSO's ERM-IF, making it the most widely-read publication about risk.…”
Section: Erm Frameworkmentioning
confidence: 98%
See 2 more Smart Citations
“…3 The target period of the literature search extends up to October 2017, as at the time of writing this paper. Many studies discuss the advantages and disadvantages of ERM frameworks (Arena, Arnaboldi, & Azzone, 2010;Beasley, Clune, & Hermanson, 2005;Choo & Goh, 2015;Hayne & Free, 2014;Karanja, 2017;Paape & Speklé, 2012;Tekathen & Dechow, 2013), and many agree with the usefulness of COSO's ERM-IF. In Fraser, Schoening-Thiessen, and Simkins (2008) survey, 74% of respondents had read COSO's ERM-IF, making it the most widely-read publication about risk.…”
Section: Erm Frameworkmentioning
confidence: 98%
“…First, studies show that ERM frameworks such as the COSO ERM-IF and ISO 31000 are factors that promote the introduction of ERM (Beasley et al, 2005;Choo & Goh, 2015;Karanja, 2017). Beasley et al (2005) showed that COSO's ERM-IF was a key factor in the ERM introduction stage statically.…”
Section: Factors That Promote or Obstruct The Introduction Of Ermmentioning
confidence: 99%
See 1 more Smart Citation
“…ERM was defined as the management of operational and financial risks simultaneously in order to maximize the costeffectiveness of risk management within the constraints of the organization's tolerance for risk (Kleffner, Lee, & McGannon, 2003). There are two main industry-sanctioned ERM models, that is, COSO 2004 and ISO 31000:2009, that organizations refer to when implementing ERM programs (Karanja, 2017).…”
Section: Enterprise Risk Management (Erm)mentioning
confidence: 99%
“…Control environment is an individual atmosphere in an organization in conducting activities and carrying out responsibility for control in its field (Rendon & Rendon, 2016;Tauringana & Mangena, 2012). Management risk assessment as a part in designing and implementing internal controls to minimize errors and fraud within an organization (de Zwaan, Stewart, & Subramaniam, 2011;Karanja, 2017). Control activities are policies and procedures developed by the organization to face risks in order to achieve organizational goals (Rama & Jones, 2008).…”
Section: Government Regulation No 60 Year 2008 On Government Internalmentioning
confidence: 99%